THE ROLE OF CLIENT SATISFACTION IN BANKING SECTOR - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
According to existing definitions and approaches, customer satisfaction can be analyzed as a general/overall judgment that a customer makes after consuming a product or a service. Customer satisfaction is perceived as “psychological state (feeling) appearing after buying and consuming a product or service (Merouane, 2009). Thus, customer satisfaction reflects “a pleasure resulting to product’s consumption, including under or over fulfillment level” (Hayes, 2012). Customer satisfaction is closely connected with a company’s success possibility now and in the future. It is acknowledged that with higher customer satisfaction level, a company could retain its customers maximally and sustain competitive advantages as well as build up customer retention and loyalty gradually in the long run (Kotler, 2006). According to Chen and Yang, (2011), customer satisfaction has increasingly gained attention from different business fields. An increasing number of companies regard customer satisfaction as a standard to measure the performance of products or services and an approach to retaining their customers. In brief, customer satisfaction is the customers’ feelings of pleasure or disappointment derived from the performance of a certain product or service related to individual expectations Kotler, (2006). Consumers have respective judgments on their purchase or consumption experience from a product or service.